2008
DOI: 10.3171/spi.2008.9.10.374
|View full text |Cite
|
Sign up to set email alerts
|

Extranodal hairy cell leukemia presenting in the lumbar spine

Abstract: The authors report on a 54-year-old man who presented with a lumbar vertebral body lesion and an adjacent epidural lesion that was found to be hairy cell leukemia (HCL). The patient presented with gradual onset of back pain and intermittent lower-extremity radicular symptoms. He did not have splenomegaly or peripheral blood count abnormalities. Admission MR imaging revealed an L-5 vertebral body lesion and a lumbar epidural lesion extending from L-3 to S-2. An [18F]fluorodeoxygluco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 7 publications
0
14
0
2
Order By: Relevance
“…Snell et al reported a patient who presented with a pathological femoral fracture 22 years after HCL diagnosis, which is the longest documented period between HCL diagnosis and subsequent bony involvement [ 30 ]. Rosen et al reported a 54-year-old man who presented with a L5 vertebral body lesion and a lumbar epidural lesion extending from L3 to S2 [ 31 ]. Biopsy sampling of the epidural mass demonstrated CD20-positive B cells that expressed TRAP and CD25, consistent with a diagnosis of HCL.…”
Section: Discussionmentioning
confidence: 99%
“…Snell et al reported a patient who presented with a pathological femoral fracture 22 years after HCL diagnosis, which is the longest documented period between HCL diagnosis and subsequent bony involvement [ 30 ]. Rosen et al reported a 54-year-old man who presented with a L5 vertebral body lesion and a lumbar epidural lesion extending from L3 to S2 [ 31 ]. Biopsy sampling of the epidural mass demonstrated CD20-positive B cells that expressed TRAP and CD25, consistent with a diagnosis of HCL.…”
Section: Discussionmentioning
confidence: 99%
“…Rosen et al described a case of a 54-year-old male who presented with severe back pain and numbness and weakness in his lower extremities [19]. The patient underwent a surgery for epidural lesion, which was later found to be HCL.…”
Section: Discussionmentioning
confidence: 99%
“…Saçlı hücreli löseminin bu şekide izole kemik tutulumu çok nadirdir. Literatürde bu durumda sadece birkaç olgu bildirilmiştir (4,(7)(8)(9). Bu açıdan bakıldığında sunduğu-muz olgu literatüre katkı sunmaktadır.…”
Section: Resim 3 Hastadan Alınan Diz Biyopsisindeki Litik Lezyonun Munclassified